Need help from an expert?
The world’s top online tutoring provider trusted by students, parents, and schools globally.
The roots of the quadratic equation 2x^2 + 3x + 1 = 0 are -1 and -0.5.
To find the roots of a quadratic equation, we can use the quadratic formula: x = (-b ± √(b^2 - 4ac)) / 2a. In this equation, a, b, and c are the coefficients of the quadratic equation ax^2 + bx + c = 0.
Using this formula for the given equation, we get:
x = (-3 ± √(3^2 - 4(2)(1))) / 2(2)
x = (-3 ± √1) / 4
Simplifying this expression, we get:
x = (-3 + 1) / 4 or x = (-3 - 1) / 4
x = -0.5 or x = -1
Therefore, the roots of the quadratic equation 2x^2 + 3x + 1 = 0 are -1 and -0.5. We can check this by substituting these values into the original equation and verifying that they make the equation true.
Study and Practice for Free
Trusted by 100,000+ Students Worldwide
Achieve Top Grades in your Exams with our Free Resources.
Practice Questions, Study Notes, and Past Exam Papers for all Subjects!
The world’s top online tutoring provider trusted by students, parents, and schools globally.